2016
DOI: 10.1136/bcr-2016-216835
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, epilepsy and polyneuropathy in a mercury-exposed patient: investigation, identification of an obscure source and treatment

Abstract: We present a patient aged 54 years with early onset of dementia, epilepsy and peripheral polyneuropathy. A mercury intoxication was diagnosed in 2010, chelation therapy with 2,3-dimercaptopropane-1-sulfonate had failed. A source of exposure could not be identified. MRI showed unspecific hyperintense brain lesions in 2015. She was referred for diagnosis and treatment. Neuropsychological testing indicated severe memory loss and nerve conduction speed measurements showed chronic neurogenically changed potentials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 7 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Measurement of other forms, such as organic mercury levels, is essential in the case of disproportionate clinical manifestation. Most of the studies on chronic symptomatic cases reported the use of skin lightening products with mercury levels exceeding 1000 ppm [3,4,[6][7][8][9][10]12,14,[16][17][18][19]37,38]. However, mercury levels as low as 6.8 ppm have been reported to produce symptoms with longer duration [32].…”
Section: Investigationmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurement of other forms, such as organic mercury levels, is essential in the case of disproportionate clinical manifestation. Most of the studies on chronic symptomatic cases reported the use of skin lightening products with mercury levels exceeding 1000 ppm [3,4,[6][7][8][9][10]12,14,[16][17][18][19]37,38]. However, mercury levels as low as 6.8 ppm have been reported to produce symptoms with longer duration [32].…”
Section: Investigationmentioning
confidence: 99%
“…Moreover, inorganic mercury has been shown to induce neuronal degeneration, which may manifest as early-onset dementia [ 9 ]. The mechanism of inorganic mercury effect on dementia is associated with its high affinity to selenium and selenoproteins.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly caused by the reduced mercury use in industry and household applications. However, multiple cases of mercury poisoning due to the use of skin-whitening creams have been reported [1][2][3][4][5][6][7]. These creams are used to achieve a lighter skin-tone, a desired ideal of beauty in many countries.…”
Section: Introductionmentioning
confidence: 99%